LAKON CARANGAN PADA PEDALANGAN SUNDA - Timbul Subagya (Gelar : Jurnal Seni Budaya, 2009)
The writing entitled lakon carangan is a descriptive review of Sundanese puppetry discussing how lakon carangan was created and the structure of it. The result of the analysis shows that lakon carangan came into existence because it was only standard stories of Mahabarata and Ramayana which were presented. To avoid boredom, puppeteers created new stories which were still based on the standard stories. The new stories are called lakon carangan. The structure of Sundanese lakon carangan is different from Javanese lakon carangan. Key words : wayang, lakon carangan, structureÂ